Traumatic arteriovenous fistula at the level of the internal iliac vessels - Mañana, Julio (2020)
1) A case of arterio-venous fistula of the large hypogastric artery and vein, is reported upon. 2) There was no hemodynamic repercussion and tolerance was good. 3) Arteriography showed the arterial radiologic features corresponding to cases of arterio-venous fistulas. 4) Surgical findings confirmed X-ray findings leading to aneurysmectomy withpreservation of th